2006
DOI: 10.1149/1.2154373
|View full text |Cite
|
Sign up to set email alerts
|

Self-Humidifying Cs2.5H0.5PW12O40 / Nafion / PTFE Composite Membrane for Proton Exchange Membrane Fuel Cells

Abstract: A Cs 2.5 H 0.5 PW 12 O 40 /Nafion/polytetrafluoroethylene ͑PTFE͒ self-humidifying composite membrane was developed for proton exchange membrane fuel cells. It was prepared by recasting the Cs 2.5 H 0.5 PW 12 O 40 /Nafion self-humidifying layer onto the two sides of a Nafion/PTFE composite membrane with a solution-recast method. Due to the strong acidic, hydrophilic, and redox properties of Cs 2.5 H 0.5 PW 12 O 40 , the Cs 2.5 H 0.5 PW 12 O 40 /Nafion self-humidifying layer not only contributes to humidify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…For example, the addition of Pt particles or HPAs allows the in situ conversion of any permeating H 2 or O 2 into water by acting through their efficient high acid catalytic activity in the peroxide decomposition [21,22]. In addition, previous works have demonstrated that HPAs have suitable properties to be used in fuel cells as solid electrolytes or aqueous solutions [23,24] and have been already introduced in perfluorinated membranes to improve the fuel cell performance [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the addition of Pt particles or HPAs allows the in situ conversion of any permeating H 2 or O 2 into water by acting through their efficient high acid catalytic activity in the peroxide decomposition [21,22]. In addition, previous works have demonstrated that HPAs have suitable properties to be used in fuel cells as solid electrolytes or aqueous solutions [23,24] and have been already introduced in perfluorinated membranes to improve the fuel cell performance [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the composite membrane has the risk of formation electron-conducting path via the network of dispersed Pt particles in the whole membrane. In the latter papers, the researchers developed Pt-containing selfhumidifying membrane mainly focusing on the following three directions: (1) decreasing the membrane thickness or incorporating some functional particles, such as SiO 2 , ZrP, and Cs 2.5 H 0.5 PW 12 O 40 to improve the cell performance under dry condition [9][10][11]; (2) designing new membranes of two-layered or three-layered structures to avoid short circuit through the membrane [12,13]; (3) using the hydrocarbon membrane which can decrease the cost of the PEM [14].…”
Section: Introductionmentioning
confidence: 99%
“…PEM lifetimes and functionality for operation in hotter and drier conditions may be enhanced by the addition of catalytic amounts of Pt or the cesium salt of 12-phosphotungstic acid, a heteropoly acid ͑HPA͒ that converts any permeating H 2 or O 2 in situ in the PEM into water. 2,3 It has been implied that any peroxide in the membrane is decomposed to water. Whereas improved fuel cell performance under hotter and drier operation has been demonstrated for MEAs containing membranes with these catalytic additives, little data exists to support the assumption that these same additives enhance PEM lifetime in a fuel cell.…”
mentioning
confidence: 99%